Climate Trends and Consumption of Foods and Beverages by Processing Level in Mexican Cities - López-Olmedo, Nancy; Diez-Roux, Ana V.; Pérez-Ferrer, Carolina; Prado-Galbarro, Francisco-Javier; Riojas-Rodríguez, Horacio; Rivera-Dommarco, Juan; Barrientos-Gutierrez, Tonatiuh (Frontiers in Nutrition, 2021)
Background: Little is known about the potential impact of climate change on food systems and diet. We aimed to estimate the association of changes in rainfall and temperatures with consumption of unprocessed and processed foods among residents of Mexican cities by climate region. Methods: We analyzed 3,312 participants of the 2012 Mexican National Health and Nutrition Survey with dietary intake and sociodemographic information linked to historical rainfall and temperature data collected by the Mexican National Weather Service. We classified foods as unprocessed, processed, or ultra-processed. We performed multilevel linear regression to estimate the association of annual change in rainfalls (for each 0.5 mm decrease) and temperatures (for each 0.1°C increase) at municipality level over the past 5 years with consumption of processed and unprocessed foods measured as the contribution to total energy intake. We investigated whether associations differed by climate region (tropical, temperate, and arid). Results: Each 0.5 mm annual decrease in precipitation was associated with lower consumption of unprocessed foods and higher consumption of ultra-processed foods [mean differences in percent contribution to total energy intake −0.009% (95% CI: −0.019, < −0.001) and 0.011% (95% CI: 0.001, 0.021), respectively]. Each 0.1 degree Celsius annual increase in temperature was also associated with lower consumption of unprocessed and higher consumption of ultra-processed foods [mean differences in percent contribution to total energy intake was −0.03 (95% CI: −0.05, −0.01) and 0.03% (95% CI: <0.01, 0.05)]. When stratified by climate region these associations were only observed in tropical regions. Conclusions: Decreases in rainfalls and increases in temperature were associated with lower consumption of unprocessed foods but higher consumption of ultra-processed foods, especially in tropical regions. Previous studies have established how food production affects the climate, our study suggests that climate change could, in turn, reinforce modern food production, closing a vicious circle with clear negative implications for planetary health.